Sistem Informasi Tracking Distribusi Surat Berbasis Web dengan Metode Agile: (Studi Kasus di Bagian Umum Pemkot Madiun) - Irvan Sanjaya; Andi Rahman Putera; Latjuba Sofyana STT (Pusat Riset dan Inovasi Nasional, 2023)
The system in place at the Regional General Secretariat of the Madiun City Government demonstrates that there have been issues with the distribution of correspondence, which is still done through printed (manual) documents, up until this point. The issues include long letter distribution processes, lost or damaged documents, and no tracking system for letter distribution operations from couriers. The Agile technique is employed in this study. Planning, design, coding and implementation, testing, and various more guidelines are all part of the Agile process using the Extreme Programming model. Agile mail distribution tracking information systems on the web are the study's outcomes. The study's conclusion is that the presence of this mechanism can facilitate tracking mail distribution for administrators, department and sub-division heads, receptionists, and couriers. Information is also easy to access because to the internet system, which makes it possible to access it from PCs, laptops, and cellphones whenever and wherever you are..